How Party-System Dynamics Shape Political Parties’ Use of Facebook Between Elections - Peter Aagaard; Sander Andreas Schwartz; Line Nygaard; Malene Teresa Larsen (Journalism and Media)
We investigate the use of Facebook in the Danish system over a two-month period in 2021, with an increased political polarization, during the COVID-19 lockdown. Based on the analysis of 5093 posts, we find indications of how party-system dynamics shape niche parties and catch-all parties’ use of Facebook. While catch-all party members share political information with relatively low reach, niche parties are much more inclined to criticize opponents, a strategy that often produces higher interactivity. Finally, we discuss the impact of party-system dynamics on the strategic use of Facebook among different parties. Our findings indicate that the social media use of niche parties with irrelevant features is often shaped by a centrifugal logic (competition towards the poles), while the social media use of catch-all parties is often shaped by a centripetal dynamic (competition towards the center).